One belt, one road, one world: where is the US business connectivity? - Roddy, Stephen; Lewis, Donald J.; Yang, Xiaohua; Moise, Diana (Henry Stewart Talks, 2019)
Belt and road initiative, Silk roads, China, Russia, USA, Fourth industrial revolution, Cyber/digital silk road, 21st Century maritime silk road, US cyber silk road, FinTech, Blue economic passages, Ice silk road, Infrastructure, Cybersecurity